2022
DOI: 10.1007/s12652-022-03805-0
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis tracking of COVID-19 vaccine through tweets

Abstract: Recent studies on the COVID-19 pandemic indicated an increase in the level of anxiety, stress, and depression among people of all ages. The World Health Organization (WHO) recently warned that even with the approval of vaccines by the Food and Drug Administration (FDA), population immunity is highly unlikely to be achieved this year. This paper aims to analyze people's sentiments during the pandemic by combining sentiment analysis and natural language processing algorithms to classify texts and extract the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Here, we compared our work with 29 significant Twitter studies [ 2 - 7 , 18 , 20 , 21 , 23 - 26 , 119 - 134 ]. Unsupervised methods, such as sentiment analysis and topic modeling, are the most popular methods used to classify and analyze tweets; 11 studies used some combination of sentiment analysis, emotion analysis, and topic modeling [ 3 , 6 , 20 , 21 , 24 , 124 , 126 , 128 , 130 , 131 , 134 ]. Most of these studies analyzed large tweet data sets comprising millions of tweets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we compared our work with 29 significant Twitter studies [ 2 - 7 , 18 , 20 , 21 , 23 - 26 , 119 - 134 ]. Unsupervised methods, such as sentiment analysis and topic modeling, are the most popular methods used to classify and analyze tweets; 11 studies used some combination of sentiment analysis, emotion analysis, and topic modeling [ 3 , 6 , 20 , 21 , 24 , 124 , 126 , 128 , 130 , 131 , 134 ]. Most of these studies analyzed large tweet data sets comprising millions of tweets.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has analyzed social media posts, particularly tweets related to COVID-19 vaccines. Here, we compared our work with 29 significant Twitter studies [2][3][4][5][6][7]18,20,21,[23][24][25][26][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Unsupervised methods, such as sentiment analysis and topic modeling, are the most popular methods used to classify and analyze tweets; 11 studies used some combination of sentiment analysis, emotion analysis, and topic modeling [3,6,20,21,24,124,126,128,130,131,134].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…The authors proposed a machine learningbased approach for sentiment analysis of COVID-19 tweets, using a dataset of 10,000 tweets that were manually annotated for the sentiment. The authors compared the performance of several machine learning algorithms, including Naive Bayes, Support Vector Machines (SVM), and Random Forest, and found that SVM achieved the best performance with an accuracy of 85.7% [15].…”
Section: Related Workmentioning
confidence: 99%
“…It is commonly used in business to establish consumer trends, such as through customer reviews [37,38]. It has been previously used in healthcare to analyze sentiments surrounding patient experience [39] and COVID-19 vaccine hesitancy [40,41]. However, the use of sentiment analysis in healthcare is lacking, perhaps in part due to insu cient domain-speci c textual data [42].…”
Section: Sentiment Analysis Of Personal Experiencementioning
confidence: 99%